تطوير نموذج تعلُّم الاستماع التفاعلي القائم على التعلُّم النشط لطلبة المستوى المبتدئ - Sanwil, Teuku (Sekolah Tinggi Ilmu Tarbiyah Al-Hilal Sigli Aceh- Indonesia, 2025)
This study aims to develop an interactive istima’ learning model based on active learning principles for beginner-level university students of Arabic. Listening skills are fundamental in Arabic language acquisition, yet many first-year students face difficulties due to teacher-centered instruction, limited interaction, and minimal exposure to authentic listening activities. This research employed a research and development design with a qualitative approach. The subjects were first-year students of the Arabic Language Education program at Sekolah Tinggi Ilmu Tarbiyah (STIT) Al-Hilal Sigli. Data were collected through observation, interviews, and documentation, and analyzed descriptively to identify learning needs, model characteristics, and implementation outcomes. The findings indicate that the proposed model emphasizes student engagement, collaborative activities, contextual listening materials, and continuous feedback, which significantly enhance students’ motivation and listening comprehension. The interactive active learning-based istima’ model encourages learners to actively process auditory input, respond critically, and participate meaningfully in classroom interaction. The study concludes that this model is effective in improving beginner students’ listening skills and can serve as an alternative instructional framework for Arabic listening courses at the university level.